1992
DOI: 10.1037/0882-7974.7.2.214
|View full text |Cite
|
Sign up to set email alerts
|

When Greta Garbo is easier to remember than Stefan Edberg: Influences of prior knowledge on recognition memory in Alzheimer's disease.

Abstract: This study investigated the effects of prior knowledge on recognition memory in patients with a mild Alzheimer's disease. Normal older adults and mildly demented patients were presented with dated and contemporary famous faces with name tags and were asked to generate unique statements about each person. Results indicated that both groups generated more statements about the dated than about the contemporary figures. Most important, both groups performed better with the dated than with the contemporary faces in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
16
0
1

Year Published

1993
1993
2001
2001

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 34 publications
6
16
0
1
Order By: Relevance
“…EXPERIMENT 2 Experiment 1 confirmed prior evidence (Backman & Herlitz, 1990;Lipinska et al, 1992) that old/new recognition is impaired in AD; music recognition is not spared in this regard. It also supported a previous indication (Backman & Herlitz, 1990) that recognition memory in AD patients differs qualitatively from that of controls.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…EXPERIMENT 2 Experiment 1 confirmed prior evidence (Backman & Herlitz, 1990;Lipinska et al, 1992) that old/new recognition is impaired in AD; music recognition is not spared in this regard. It also supported a previous indication (Backman & Herlitz, 1990) that recognition memory in AD patients differs qualitatively from that of controls.…”
Section: Discussionsupporting
confidence: 70%
“…The authors concluded that one symptom of AD is an inability to use task-relevant prior knowledge to aid episodic remembering, even when that knowledge is relatively rich. However, in a follow-up study, Lipinska, Backman, and Herlitz (1992) used procedures that encouraged more elaborative encoding at the time of study (faces were accompanied by their names, and subjects attempted to generate facts about each person). In that study, the AD patients showed improved performance, as well as the theoretically critical advantage of dated faces over contemporary faces.…”
mentioning
confidence: 99%
“…Similarly, when taxonomic category cues were provided as retrieval support for recall of organizable words, both groups showed an improvement in performance relative to free recall (36). Furthermore, as has been demonstrated in normal elderly adults (17, 45,46), both groups showed better episodic recognition with dated than with contemporary famous faces. Thus, it appears as if subjects with SDD are able to utilize cognitive support in the form of organization, category cues and previous knowledge in order to enhance episodic memory in the same way as normal elderly adults.…”
Section: Discussionsupporting
confidence: 54%
“…Subsequent research has extended these findings by demonstrating performance gains in AD patients when cues were presented at retrieval following the provision of encoding support in the form of requirements of motor activity (18), a rich stimulus input through the use of real-life objects (19), inherent organizability of the materials (20), explicit linkage of target item and cue (21), and self-generation activity (22). Similarly, AD patients have been found to be able to utilize prior knowledge to boost episodic recognition of famous faces, although the activation of underlying knowledge structures needs to be stronger than that which applies in normal aging (23,24). A summary of this research is provided in Table 1.…”
Section: Potential For Memory Improvementmentioning
confidence: 99%